Does a hospital culture influence adherence to infection prevention and control and rates of healthcare associated infection? A literature review. Issue 1 (January 2019) - van Buijtene, Adriana; Foster, Dona
Background: Over 4 million patients acquire a healthcare-associated infection (HCAI) in Europe every year, indicating possible shortcomings in hospitals converting evidence-based infection prevention and control (IPC) strategies into universal adherence. We present a literature review exploring whether insufficient adherence could be culturally based. Aim: To find empirical evidence if and how specific traits of organisational culture improve adherence to IPC strategies utilising HCAI rates as the marker of system failures or successes. Methods: PubMed, CINAHL, PsycINFO and the British Nursing index database were searched from January 2007 to June 2018. Hand-searching, Google Scholar and the snowball effect completed the investigation. The quality of the studies was assessed with the guidance of CASP and Cochrane tools. Results: Twenty papers were eligible for data extraction and thematic analysis. Studies predominantly report positive findings for the association, but none were determined high quality due to multiple methodological concerns. Analysing both quantitative and qualitative research revealed eight major themes: hospital cultures with better HCAI rates foster safety culture; have a generative leadership style; embrace innovation; ensure interventions fit local context; accept long-term orientation; engage and empower health professionals; promote collaboration and communication; and see the benefits of a non-punitive climate. Interpretation: The literature linking organisational culture and HCAI rates is suggestive, but not conclusive, indicating caution about their inferences. Leaving cultural growth to chance or allowing for weak or toxic cultures impedes on our IPC strategies and equivalently our HCAI rates.